Tenebrio molitor Proteins-Derived DPP-4 Inhibitory Peptides: Preparation, Identification, and Molecular Binding Mechanism - Jiao Tan; Jing Yang; Xinyi Zhou; Ahmed Mahmoud Hamdy; Xilu Zhang; Huayi Suo; Yu Zhang; Ning Li; Jiajia Song (Foods, 2022)
Inhibition of dipeptidyl peptidase-4 (DPP-4) is an effective way to control blood glucose in diabetic patients. Tenebrio (T.) molitor is an edible insect containing abundant protein. T. molitor protein-derived peptides can suppress the DPP-4 activity. However, the amino acid sequence and binding mechanism of these DPP-4 inhibitory peptides remain unclear. This study used the flavourzyme for T. molitor protein hydrolysis, identified the released peptides with DPP-4 inhibitory effect, and investigated the binding interactions of these peptides with DPP-4. The results showed that flavourzyme efficiently hydrolyzed the T. molitor protein, as demonstrated by the high degree of hydrolysis, disappearance of protein bands in SDS-PAGE, and changes to protein structure. The 4-h flavourzyme hydrolysates showed a good inhibitory effect on DPP-4 (IC50 value of 1.64 mg/mL). The fragment of 1000–3000 Da accounted for 10.39% of the total peptides, but showed the strongest inhibitory effect on DPP-4. The peptides LPDQWDWR and APPDGGFWEWGD were identified from this fraction, and their IC50 values against DPP-4 were 0.15 and 1.03 mg/mL, respectively. Molecular docking showed that these two peptides interacted with the DPP-4 active site via hydrogen bonding, hydrophobic interactions, salt bridge formation, π-cation interactions, and π-π stacking. Our findings indicated that T. molitor protein-derived peptides could be used as natural DPP-4 inhibitors.